The Peak of Noncentral Stirling Numbers of the First Kind - Roberto B. Corcino; Cristina B. Corcino; Peter John B. Aranas (International Journal of Mathematics and Mathematical Sciences)
We locate the peak of the distribution of noncentral Stirling numbers of the first kind by determining the value of the index corresponding to the maximum value of the distribution.